Effect Of Farmer Behavior On Farming Productivity Of Porang (Amorphophallus Oncophyllus Prain) In Tegalwaru District Karawang - Sri Shinta Paulina; Sulistyo Sidik Purnomo; I Putu Eka Wijaya (UNIVED Press, Dehasen University Bengkulu, 2023)
Porang is a food crops that has high economic value. Porang production still cannot be fulfilled optimally. The productivity of farmers in managing farming is very dependent on their behavior such as: knowledge, attitudes, and skills of farmers. This study aims to: (1) analyze the influence of farmer behavior both farmer knowledge, farmer attitudes and farmer skills simultaneously on people's productivity; (2) Analyzing the influence of farmer behavior, be it farmer knowledge, farmer attitudes or farmer skills partially on people's productivity. The research method used is descriptive quantitative method. The number of research respondents was 30 porang farmers purposively with the determination of sampling using the saturated sample method. The collection of research data using primary data through interviews with questionnaires, while secondary data obtained from agencies related to research. The analysis technique used is classical assumption test, multiple linear regression analysis, and hypothesis testing. The results showed that the hypothesis test of farmer behavior (knowledge, attitudes, and skills) simultaneously had a significant effect on people's productivity with a Fcount of 5.035 > Ftable of 2.960 and a significance value of 0.007 < a significance of 0.05. Partially, aspects of knowledge and aspects of attitude have a significant effect on people's productivity with successive tcount values ​​of 2.318 and 2.206 > ttable of 2.056 and 2.056 respectively. While the skill aspect has no significant effect on the productivity of people in Tegalwaru District, Karawang Regency with a tcount of 0.215 <ttable of 2.056. Keywords : attitude; knowledge; porang; productivity; skill